The Role of Failing Autonomic Nervous System on Life-Threatening Idiopathic Systemic Capillary Leak Syndrome - Colombo, Riccardo; Wu, Maddalena Alessandra; Catena, Emanuele; Perotti, Andrea; Fossali, Tommaso; Cioffi, Federico; Rech, Roberto; Castelli, Antonio; Cicardi, Marco (Frontiers in Medicine, 2018)
Idiopathic systemic capillary leak syndrome (ISCLS) is a rare disease that involves the endothelium and microcirculation, leading to an abrupt shift of fluids and proteins from the intravascular to the interstitial compartment. The consequence of the capillary leakage is a life-threatening hypovolemic shock that can lead to lethal multiple organ dysfunction. The autonomic nervous system (ANS) is central in regulating the cardiovascular response to hypovolemia, but ANS modulation in ISCLS has not yet been investigated. Here, we report ANS activity during acute phase and recovery from a severe ISCLS shock and speculate on the possibility that autonomic mechanisms underlie the pathogenesis of attacks.